Isolation of local bacterial capable of degrading halogenated compounds and analysis of putative haloacid permease gene [electronic resource] - 292257 Ng, Hong Jing; Fahrul Zaman Huyop, supervisor (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Biosains)) - Universiti Teknologi Malaysia, 2006